Increasing Students' Interest in Reading in Libraries in Elementary Schools - Maharani, Anggi Ditami; Putri, Tasya Billah; Fadhlan, Muhammad Rizky (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
Interest is the nature of a person's desire and willingness to carry out activities without any element of coercion in it. Interest is a sense of like and a sense of interest in something you want to learn and also a person's tendency to do the activity he wants. Reading is one of the important and decisive skills in academic activities by reading a learner will train and develop the logic of thinking so that it can respond scientifically to phenomena the learning process at various levels of education also always demands mastery of reading skills for students. The library is a space that provides various books for students so that they can foster interest in reading in the library, where the library stores a myriad of knowledge that students can learn to increase knowledge and insight and information that can be taken from reading books. The method used in this research is a quantitative method of literature study. The purpose of schools that apply their students to always go to the library is to increase students' interest in reading, to be trained in reading and in addition to gaining the benefits of knowledge and experience, students will also gain insight from book reading activities carried out by students in the school library.